Lost in traffic: consequences of altered palmitoylation in neurodegeneration - Ramzan, Firyal; Abrar, Fatima; Mishra, Gyana Gourab; Liao, Lucia Meng Qi; Martin, Dale D. O. (Frontiers in Physiology, 2023)
One of the first molecular events in neurodegenerative diseases, regardless of etiology, is protein mislocalization. Protein mislocalization in neurons is often linked to proteostasis deficiencies leading to the build-up of misfolded proteins and/or organelles that contributes to cellular toxicity and cell death. By understanding how proteins mislocalize in neurons, we can develop novel therapeutics that target the earliest stages of neurodegeneration. A critical mechanism regulating protein localization and proteostasis in neurons is the protein lipid modification S-acylation, the reversible addition of fatty acids to cysteine residues. S-acylation, more commonly referred to as S-palmitoylation, or simply palmitoylation, is the addition of a 16-carbon fatty acid to proteins. Similar to phosphorylation, palmitoylation is highly dynamic and tightly regulated by writers (i.e., palmitoyl acyltransferases) and erasers (i.e., depalmitoylating enzymes). The hydrophobic fatty acid anchors proteins to membranes, thus, the reversibility allows proteins to be re-directed to and from membranes based on local signaling factors. This is particularly important in the nervous system where axons (output projections) can be meters long. Any disturbance in protein trafficking can have dire consequences. Indeed, many proteins involved in neurodegenerative diseases are palmitoylated, and many more have been identified in palmitoyl-proteomic studies. It follows that palmitoyl acyl transferase enzymes have also been implicated in numerous diseases. In addition, palmitoylation can work in concert with cellular mechanisms, like autophagy, to affect cell health, as well as with protein modifications, such as acetylation, nitrosylation, and ubiquitination, to affect protein function and turnover. Limited studies have further revealed a sexually dimorphic pattern of protein palmitoylation. Therefore, palmitoylation can have wide-reaching consequences in neurodegenerative diseases.